2020
DOI: 10.1155/2020/9531549
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of TIGIT/CD57 in Peripheral Blood/Bone Marrow NK Cells in Patients with Chronic Myeloid Leukemia

Abstract: The antitumor activity of NK cells in patients with chronic myeloid leukemia (CML) is inhibited by the leukemia microenvironment. Recent studies have identified that the expression of TIGIT, CD57, and KLRG1 is related to the function, maturation, and antitumor capabilities of NK cells. However, the characteristics of the expression of these genes in the peripheral blood (PB) and bone marrow (BM) from patients with CML remain unknown. In this study, we used multicolor flow cytometry to assay the quantity and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
3
8
1
Order By: Relevance
“…This result is the same as our observation in CML patients, 34 indicating that there were more mature NK cells that accumulate in the BM of AML-DN patients, which may impact patient survival. Previously, Chretien et al divided AML patients into three subtypes based on NK cell maturation and found that patients with more immature NK cells had reduced relapse-free and overall survival, suggesting that diseaseinduced alterations in NK cell maturation affect patient outcome.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This result is the same as our observation in CML patients, 34 indicating that there were more mature NK cells that accumulate in the BM of AML-DN patients, which may impact patient survival. Previously, Chretien et al divided AML patients into three subtypes based on NK cell maturation and found that patients with more immature NK cells had reduced relapse-free and overall survival, suggesting that diseaseinduced alterations in NK cell maturation affect patient outcome.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we were surprised to find that CD56 dim CD57 + NK cells accumulate in the BM of AML‐DN patients but not in PB. This result is the same as our observation in CML patients, 34 indicating that there were more mature NK cells that accumulate in the BM of AML‐DN patients, which may impact patient survival. Previously, Chretien et al.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, NK cells display low expression of NCR, NKG2C, NKG2D in CML, which is rejuvenated post-TKI ( 101 , 107 , 108 ). Expression of inhibitory molecules (PD-1, TIGIT) appear to be elevated in de novo CML, and these levels change in individuals achieving a molecular response ( 109 , 110 ). A significant decrease in NKG2D and DNAM-1 expression was observed in MDS, and was associated with the impaired killing of MDS blasts ( 111 ).…”
Section: Innate Immunity In Myeloid Malignanciesmentioning
confidence: 99%
“…To evade this, AML cells express low levels of CD155 and CD112 which results in attenuation of NK cell cytolytic towards AML blasts [ 91 , 92 ]. Similarly, TIGIT expression was observed on CD57+ NK cells in CML which might be a reason of NK cell dysfunction in CML [ 93 ]. Similar results were obtained in studies on TIGIT in AML [ 94 , 95 ].…”
Section: Leukemia-derived Factors That Promote Immune Evasionmentioning
confidence: 99%